2008
DOI: 10.1145/1352322.1352207
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pair-programming on individual programming skill

Abstract: Previous studies have reported significant educational benefits from the use of pair-programming, in which two students program together at the same computer. Here, we report the results of a controlled study designed to measure the effects of pair-programming on the development of individual programming ability. Our findings indicate significant improvements in individual programming skill for students with lower SAT scores. Additionally, we found that all students are more likely to complete the course succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…The students switch over being driver and navigator throughout the assignment. Pair programming has been effectively used in the classroom [15] and is an effective way to encourage students to engage in confident practice while learning and consequently doing better in their programming. [16] Coding Dojos [17] harken back to something like the masterapprentice model to support acculturation.…”
Section: Related Workmentioning
confidence: 99%
“…The students switch over being driver and navigator throughout the assignment. Pair programming has been effectively used in the classroom [15] and is an effective way to encourage students to engage in confident practice while learning and consequently doing better in their programming. [16] Coding Dojos [17] harken back to something like the masterapprentice model to support acculturation.…”
Section: Related Workmentioning
confidence: 99%
“…This activity needs the students have to interact closely with each other [18]. In such circumstance, pairing the students plays a major role for the effective learning [4], [10]. The student's choice of pair partner depends on many social factors such as the personality [16], [32], academic achievement [15], gender, and mother tongue of the other partner.…”
Section: Personality Conflictsmentioning
confidence: 99%
“…It is a well-known pedagogical technique for teaching introductory programming. Studies have shown that students who pair program produce higher quality code [11], show greater confidence in their solutions [6,14], are more likely to pass their programming courses [2,14,15], and are more likely to persist in the major [4,14] than solo programmers. Pair programming is also thought to be particularly beneficial for women students because it dispels perceptions that programming is a competitive, socially isolating activity [22].…”
Section: Introductionmentioning
confidence: 99%